Standardization of extracellular vesicle measurements by flow cytometry through vesicle diameter approximation - van der Pol, E.; Sturk, A.; van Leeuwen, T.; Nieuwland, R.; Coumans, F.; Mobarrez, F.; Arkesteijn, G.; Wauben, M.; Siljander, P. R.‐M.; Sánchez‐López, V.; Otero‐Candelera, R.; Ramón, L. A.; et al. (Journal of thrombosis and haemostasis, 2018)
Essentials Platelet extracellular vesicles (EVs) concentrations measured by flow cytometers are incomparable. A model is applied to convert ambiguous scatter units to EV diameter in nanometer. Most included flow cytometers lack the sensitivity to detect EVs of 600 nm and smaller. The model outperforms polystyrene beads for comparability of platelet EV concentrations. Summary Background Detection of extracellular vesicles (EVs) by flow cytometry has poor interlaboratory comparability, owing to differences in flow cytometer (FCM) sensitivity. Previous workshops distributed polystyrene beads to set a scatter‐based diameter gate in order to improve the comparability of EV concentration measurements. However, polystyrene beads provide limited insights into the diameter of detected EVs. Objectives To evaluate gates based on the estimated diameter of EVs instead of beads. Methods A calibration bead mixture and platelet EV samples were distributed to 33 participants. Beads and a light scattering model were used to set EV diameter gates in order to measure the concentration of CD61–phycoerythrin‐positive platelet EVs. Results Of the 46 evaluated FCMs, 21 FCMs detected the 600–1200‐nm EV diameter gate. The 1200–3000‐nm EV diameter gate was detected by 31 FCMs, with a measured EV concentration interlaboratory variability of 81% as compared with 139% with the bead diameter gate. Part of the variation in both approaches is caused by precipitation in some of the provided platelet EV samples. Flow rate calibration proved essential because systems configured to 60 μL min−1 differed six‐fold in measured flow rates between instruments. Conclusions EV diameter gates improve the interlaboratory variability as compared with previous approaches. Of the evaluated FCMs, 24% could not detect 400‐nm polystyrene beads, and such instruments have limited utility for EV research. Finally, considerable differences were observed in sensitivity between optically similar instruments, indicating that maintenance and training affect the sensitivity.